Integrasi Al-Quran dan Sains sebagai Ciri Khas Madrasah: Sebuah Persepsi Guru IPA Madrasah Tsanawiyah - Adelia Alfama Zamista; Milya Sari; Pipi Deswita; Allan Asrar (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
The integration of the Qur'an and science is one of the characteristics of madrasah. However, there are differences of opinion among teachers about the obligation to carry out science learning that is integrated with the Qur'an. For this reason, it is necessary to conduct research on how teachers perceive the integration of the Qur'an and science in learning. This study uses a quantitavie approach. The data collection method was through the survey by giving questionnaires to teachers who are members of the MGMP IPA MTs throughout the city of Padang. Of the 50 teachers who are members of the MGMP there are 47 teachers who fill out the questionnaire. Data analysis was carried out descriptively. The results of this study indicate that the majority of teachers agree that the form of the relationship between science and the Koran is integrated. However, in implementing the integration of Al-Quran and Science, it should not only be the responsibility of the science teacher, but also the role of the religious teacher. Teachers also feel the need to take part in various trainings in order to be able to carry out science learning that is integrated with the Qur'an properly.